A New Giant Parabathynellid from Cambodia (Syncarida: Bathynellacea). Issue 4 (1st July 2015) - Cho, Joo-Lae; Kry, Masphal; Chhenh, Kimsun
Abstract: Kampucheabathynella n. gen. is erected for a new species, K. khaeiptouka, from a well located in the Mekong basin of Cambodia. An illustrated description of the new genus and the new species are provided. The new genus stands out from other representatives of Parabathynellidae by its 10-segmented antennule, 7-segmented antenna, seta-like tooth of the mandible, the absence of the first pleopod, the uropod with sympod having numerous (up to 25 spines) spines, with endopod having two terminal spines of similar size and the pleotelson with one dorso-lateral seta situated at a distance from the base of each furcal ramus on both sides. The male thoracopod VIII is more or less oval in lateral view, twice as long as wide, with massive protopod displaying prominent penial region with terminal opening and nine teeth on dentate lobe. Its epipod (= outer lobe) is conical, rounded terminally and the distal part barely reaches the penial region of protopod. The basis is as big as penial region, without basipodal setae and its inner margin is drawn out to a round projection. The exopod is half as long as the basis, semilunar in lateral view, and with an apical setule.